Central Bank Balances and Reserve Requirements - Gray, Simon (IMF Working Papers; Working Paper ;, 2011)
Most central banks oblige depository institutions to hold minimum reserves against their liabilities, predominantly in the form of balances at the central bank. The role of these reserve requirements has evolved significantly over time. The overlay of changing purposes and practices has the result that it is not always fully clear what the current purpose of reserve requirements is, and this necessarily complicates thinking about how a reserve regime should be structured. This paper describes three main purposes for reserve requirements - prudential, monetary control and liquidity management - and suggests best practice for the structure of a reserves regime. Finally, the paper illustrates current practices using a 2010 IMF survey of 121 central banks.